Seromucinous Hamartoma of the Lateral Nasal Wall with Infiltration of the Orbit: A Rare Case Report and Review of the Literature - Lentiona Basiari; Maria Michali; Ioannis Komnos; Georgios Tsirves; Victoria Tsoumani; Ioannis Kastanioudakis (Case Reports in Otolaryngology)
Seromucinous hamartoma is a rare benign glandular proliferation arising from the respiratory epithelium of the sinonasal tract and nasopharynx. It was described for the first time in 1974 by Baillie and Batsakis. Since then, few cases have been reported in the literature with most of them occurring in the posterior nasal septum. We report the case of a 52-year-old woman that presented to our department with left periorbital edema, pain, and dacryorrhea due to seromucinous hamartoma arising from the left inferior turbinate and extending through the lateral nasal wall into the maxilla, the nasolacrimal duct, and the orbit. Endoscopic medial maxillectomy and endoscopic transnasal orbital tumor resection were performed. The patient remains symptom-free for 16 months, till her most recent follow-up. Seromucinous hamartoma of the nasal cavity is an exceedingly rare diagnosis, especially in the lateral nasal wall. It should be included in the differential diagnosis of nasal tumors. According to the literature review, this is the first case report of seromucinous hamartoma with orbit infiltration. Endonasal endoscopic resection is the treatment of choice.